PELEPASAN DAN PENGADAAN TANAH UNTUK KEPENTINGAN UMUM TANAH KAS DESA SAWAHAN KECAMATAN NGEMPLAK KABUPATEN BOYOLALI DALAM RANGKA PEMBUATAN JALAN - TAUFIK ADHI WICAKSONO (RECHTSTAAT, 2014)
This study aims to know knowing because the land acquisition cash viilage Sawahan, common interests in the village sub-districts Ngemplak, district Boyolali and to know the recruitment process due to the village as a substitute for land acquisition viilage Sawahan, common interests in the village sub-districts Ngemplak, district Boyolali. This includes legal writing research empirical juridical, legal materials collection techniques by means of studies and interviews with library and using qualitative methods of analysis. Based on the research process land buying process cash village because the public interest in the village Sawahan, sub-district Ngemplak, regency Boyolali because the public interest includes several phases land acquisition was conducted in a deliberative manner to obtain an agreement between committee land acquisition with the proprietor of land. The village government Sawahan propose discharge to a 's consultative village to ask for approval from the presence of the release of the right. While the land acquisition process cash village substitute as because of land acquisition village because the public interest in the village sawahan, sub-district Ngemplak, regency Boyolali are in accordance with the presidential number 36 0f 2005 on land acquisition for the implementation of development for public interest. The land acquisition process cash village a substitute for as a result of the land acquisition village because of common interests in the village of sawahan, sub-district ngemplak, district boyolali covering inventorying and identification mastery, the possession of; use, and a utilization of land, an assessment of compensation, deliberation the provision of compensation, the release of land, successor, land acquisition evaluation of land acquisition, the provision of their land compensation a substitute for cash and its use in the future. Keyword : Land acquisition, Compensation, The land of cash village